Exploring emotionality, and civic empowerment and engagement in online participation: A case study of community reporting website Homicide Watch DC. Issue 1 (February 2016) - Barnes, Renee
This article explores the emotional dimension of online audience participation in relation to crime reporting. Traditionally, crime reporting has been analysed in relation to how it is framed and the impact this has on audience perceptions of crime. However, drawing on a case study of community reporting website Homicide Watch DC, this article will explore the role of meaningful audience engagement in crime reporting and in particular the role of emotionality in this participation, specifically as a catalyst for civic empowerment and ultimately civic engagement.